The Winnipeg General Strike - Balawyder, Aloysius (Copp-Clark, 1967)
The Winnipeg General Strike is undoubtedly one of the most controversial events in Canadian history. Many Canadian newspapers and a considerable portion of correspondence among the federal, provincial and municipal officials claimed that strike was inspired by the Bolsheviks who allegedly aimed to create a soviet in Winnipeg. On the other hand, the majority of the strikers as well as labour leaders contended that strike was a last-resort weapon used by the workers to gain the rights of collective bargaining and to obtain higher wages. Documents, newspapers editorials, and extracts from critical works have been selected for giving the students a relatively complete picture of government and public opinion of the causes, events and effects of this strike. There has been one notable exception, for no excerpt from the Robson Report is included in this volume. --From author's preface
Keywords: General Strike, Winnipeg, Man., 1919